2023
DOI: 10.1039/d3cp00088e
|View full text |Cite
|
Sign up to set email alerts
|

Two-dimensional XY ferromagnetism above room temperature in Janus monolayer V2XN (X = P, As)

Abstract: Two-dimensional (2D) XY magnets with easy magnetization planes support the nontrivial topological spin textures whose dissipationless transport is highly desirable for 2D spintronic devices. Here, we predicted that Janus monolayer...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 65 publications
1
5
0
Order By: Relevance
“…Previous studies of elemental iron show that the local magnetic moments are present due to Hund interaction and contribute essentially to thermodynamic and magnetic properties [34][35][36][37][38]. The pristine Fe 2 C is expected to posses XY (easy-plane) magnetic anisotropy [29], and therefore, if it possesses local magnetic moments as in the elemental iron, it is expected to show the corresponding Berezinskii-Kosterlitz-Thouless (BKT) transition and finite magnetization in finite-size samples, similarly to that recently observed in CrCl 3 [39] and suggested for other Janus monolayers [40,41]. Also, it was suggested that the anisotropy of Fe 2 C can be changed to easy-axis by the external electric field [32], deformation [33], and introducing layered geometry [42].…”
Section: Introductionsupporting
confidence: 65%
“…Previous studies of elemental iron show that the local magnetic moments are present due to Hund interaction and contribute essentially to thermodynamic and magnetic properties [34][35][36][37][38]. The pristine Fe 2 C is expected to posses XY (easy-plane) magnetic anisotropy [29], and therefore, if it possesses local magnetic moments as in the elemental iron, it is expected to show the corresponding Berezinskii-Kosterlitz-Thouless (BKT) transition and finite magnetization in finite-size samples, similarly to that recently observed in CrCl 3 [39] and suggested for other Janus monolayers [40,41]. Also, it was suggested that the anisotropy of Fe 2 C can be changed to easy-axis by the external electric field [32], deformation [33], and introducing layered geometry [42].…”
Section: Introductionsupporting
confidence: 65%
“…60 To deal with the strongly correlated 3d orbitals of V, the Hubbard correction was used with a U value of 4.0 eV. 47 In previous works, U = 1-4 eV [61][62][63][64][65] for V-d orbitals had been adopted. Therefore, in the ESI †, we demonstrated the effect of varying the values of the U parameters on key electronic and magnetic properties of these materials (Fig.…”
Section: Methodsmentioning
confidence: 99%
“…45 Moreover, the Janus monolayers 2H-VSSe, 2H-VSeTe, and 2H-VSTe demonstrate enhanced structural stability compared to the unstable monolayer 2H-VSe 2 . 46,47 Hence, the incorporation of Janus characteristics into monolayer magnets offers a distinctive avenue for uncovering novel 2D magnetic materials with exceptional properties. Recently, R. T. Sibatov et al introduced an asymmetric 2D Janus structure known as XMoSiN 2 , which is derived from the MoSi 2 N 4 monolayer.…”
Section: Introductionmentioning
confidence: 99%
“…The successful synthesis of Janus MoSSe and WSSe by controlling reaction conditions in experiments 20,21 provides a novel approach to the design of 2D FM materials. For example, monolayer Janus Cr 2 I 3 X 3 (X = Br, Cl), 22 VSSe, 23 and VSCl 24 are reported to be FM semiconductors, and FeXY (X, Y = Cl, Br, I), 25 V 2 XN (X = P, As) 26 are calculated to be FM metals. Furthermore, it is worth noting that experimentally synthesized VI 3 has a T C of only 50 K, while Janus structures such as V 2 Cl 3 I 3 can elevate the T C to 240 K. 27 Similarly, the FM coupling in monolayer Janus Fe 2 I 3 Cl 3 is stronger than that in FeI 3 , resulting in an increase in T C from 77 K (FeI 3 ) to 260 K, which indicates the potential to achieve room-temperature magnetism from 2D Janus materials.…”
Section: Introductionmentioning
confidence: 99%